‘Clio & Members’: the research of the education of the history in Argentina - Coudannes, Mariela (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
The present article recovers the trajectory of the magazine Clio and Members. The taught history edited in a joint way for the National University of Litoral and the National University of La Plata (Argentina). It describes the motivations that led to its creation in 1996; it has a strong emphasis on the need to assess in a critical way the progress of educational reform in the school and its impact on the development for educators in the university. Then, it gives a thorough review on the main issues and problems that were taken into account during its sixteen numbers, such as education from a gender perspective or the construction of a current history in the classroom. The knowledge management of his contributions allows to affirm that the magazine “ Clío and Members ” has had a very excellent role in the shape and consolidation of research in the field of didactics of the history in this country.